Pendampingan Masyarakat dalam Pembuatan Nomor Induk Berusaha (NIB) untuk Pengembangan UMKM melalui Online Single Submission (OSS): Pengabdian kepada Masyarakat di Desa Imbanagara Raya-Ciamis - Sumarni, Sumarni; Aristhantia, Isti Tresna; Nursafitri, Desi; Laelasari, Siska; Nurani, Rani (Khidmat, 2023)
This community service article focuses on efforts to support the creation of a Business Identification Number in the village of Imbanagara Raya. To date, the community in Imbanagara Raya Village is still unaware of the importance of business legality, one of which is the Business Identification Number (NIB), resulting in a lack of consumer confidence. This service method is carried out using the door-to-door method, an approach where the officers and the assistance team in this case go directly to the business actors or the homes of business actors in Imbanagara Raya Village to provide socialisation, understanding and guidance in the process of making the NIB. After the assistance and engagement, it can be seen that the results of 250 MSMEs do not have NIB, after this service as many as 230 MSMEs in Imbanagara Raya village already have NIB.